Live play, live sex: The parallel labors of video game live streaming and webcam modeling. (December 2022) - Ruberg, Bo
This article looks at two forms of online self-broadcasting: webcam modeling and video game live streaming. Though these practices have much in common, the parallels between them have gone largely unacknowledged, in part because the discriminatory cultures surrounding video games have rendered connections between streaming and sex work unspeakable. Drawing from an analysis of "tips and tricks" YouTube videos created by women webcam models and men live streamers, this research maps the relationship between camming and streaming as forms of labor. It illustrates the many overlaps between the two practices, challenging notions that camming is inferior to or even separate from streaming.